A comparative study of albumin-bilirubin score, MELD and Child Pugh scores for predicting the in-hospital mortality in cirrhotic patients complicated with Upper GI bleeding in a Tertiary care hospital - Nagaraja, B.S.; Madhumati, R.; Umesh, K.J.; Rashwith, U. (Asian Journal of Medical Sciences, 2018)
Background: Alcoholic liver Disease (ALD) encompasses a spectrum of Injury, ranging from simple steatosis to frank cirrhosis which is evaluated by many scoring systems. Aims and Objective: Our study aims at evaluating the discriminative abilities of Child-Pugh, model for end-stage liver disease (MELD), and albumin-bilirubin (ALBI) scores in predicting the inhospital mortality in cirrhotic patients complicated with acute upper gastrointestinal bleeding. Materials and Methods: Data of Patients with Liver cirrhosis secondary to ethanol presented with Upper GI bleed were retrospectively reviewed. Child Pugh, MELD and ALBI scores were calculated for the patients and results from ROC curves were analysed. Results: In our study conducted on 112 patients, the age distribution was between 18-74 yrs with mean age of patients being 46.47+/-10.9 years, sex ratio Male: Female: 105:7 with mortality rate of 33.4%.the Area under curves of ROC of ALBI, Child Pugh and MELD are 0.743, 0.864 and 0.763. Conclusion: The prognostic performance of all 3 scores was comparable but Child Pugh score was found to have better prognostic significance than ALBI and MELD score.